Pengaruh Komitmen Organisasi, Gaya Kepemimpinan Dan Komunikasi Kerja Terhadap Kinerja Karyawan (Studi Kasus CV. Engkok Soki) - Syaipullah Syaipullah; Afi Rahmat Slamet; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study is to examine the influence of the Organizational Committee, Leadership Styles, and Work Communication on Employee Performance in PT. CV. Angkok Soki. This study uses quantitative research. The data used were primary data obtained using a questionnaire by taking a population sample of 42 respondents.This study used analytical SPSS using tools such as Validity, Reliability, Normality Test, Heteroscedasticity Test, Multicolority Test, Multiple Regression Test, F Test, and T Test and measured using Likert scale. Where the results of the analysis depend on the scores obtained from the respondents.The results of this study are (1) Organizational Commitment has no significant impact on employee performance (2) Leadership style has an apositive and significant impact on employee performance (3) Work Communication has a positive and significant impact on employee performance. Keywords:Organizational Comitment, Leadership Style, Work Communication Performance.